THE EFFECT OF RELATIONAL SATISFACTION AND SERVICE SATISFACTION ON CUSTOMER LOYALTY WITH COMMITMENT AS A MEDIATING VARIABLE (CASE STUDY: JNE SERVICE USER IN YOGYAKARTA CITY) - IBN Udayana; Lusia Tria Hatmanti Hutami; feri irawan (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2023)
AbstractThis research was conducted with the aim of identifying and analyzing consumer interest in the use of JNE service delivery services. with several related variables in this study are relatioal satisfaction, servive satisfaction, consumer loyalty as a bound variable and commitment variable as a mediation variable. the population in this study used 123 respondents who used JNE services with 123 samels used for the study and with data collection was carried out using the google form questionnaire dissemination method. The results of this study are that relational satisfaction has a positive effect on loyalty; service satisfaction has a positive effect on loyalty; relational satisfaction, service satisfaction has a positive effect on commitment; and commitment as a mediation has a positive effect on customer loyalty.